Effect of paracetamol and celecoxib on the state of hemocoagulation in the most acute period of heat injury in rats - Chuykova, P.O.; Shtrygol’, S.Yu.; Lebedynets, I.O.; Lytkin, D.V. (Medicni Perspektivi, 2025)
Acute heat injury (AHI) occurs due to exposure to high environmental temperatures and is considered a dangerous condition that requires effective prevention and treatment. This underscores the importance of searching for and thoroughly studying thermoprotective agents. Previous studies on a rat model of AHI have shown that the highly selective cyclooxygenase-2 (COX-2) inhibitor celecoxib and the analgesic-antipyretic paracetamol effectively prevent hyperthermia, but celecoxib, unlike paracetamol, improves the functional state of the central nervous system during the recovery period. Since AHI induces blood coagulation disturbances, it is important to determine the effects of these thermoprotective agents on hemostasis. The aim of this study was to investigate the effects of paracetamol and celecoxib as effective thermoprotectors on coagulation parameters during the acute phase of heat trauma in rats. The AHI model was reproduced оn adult white male rats through a 30-minute exposure to +55°C. The animals were divided into four groups of 7-8 rats each: intact control, pathological control, celecoxib group (8.4 mg/kg intragastrically 50-60 minutes before heat exposure), and paracetamol group (125 mg/kg in the same regimen). Rectal temperature was monitored, and in rat plasma, fibrinogen, prothrombin time (PT), thrombin time (TT), activated partial thromboplastin time (APTT) were determined, while D-dimer was measured in serum. The results showed that during the acute phase of AHI in the pathological control group, when body temperature increased by an average of 4.33±0.33°C (p<0.01 compared to baseline), fibrinogen, PT, TT, and APTT levels remained unchanged, but the D-dimer level in serum increased by 2.2 times, indicating enhanced thrombogenesis. Both celecoxib and paracetamol exhibited a statistically significant thermoprotective effect (temperature rise of 3.16±0.40°C and 3.21±0.12°C, respectively, p<0.01 compared to untreated animals), had no effect on fibrinogen, PT, TT, or APTT levels, but normalized the D-dimer level, indicating an antithrombotic effect. The results justify the use of COX inhibitors, particularly celecoxib, in AHI.